0727 Study Onthe Effect Of Obstructive Sleep Apnea-hypopnea Syndrome Onperioperative Management Inendoscopic Sinussurgerypatients. (27th May 2020) - Xiaojun, Z; Chan, W; Hao, W; Fang, F; Wei, X
Abstract: Introduction: To determine the frequency of undiagnosed OSA patients in patients received endoscopic sinus surgery (ESS) and to investigate the effect of OSA on the perioperative management in those patients. Methods: 308 patients undergoing ESS from 2017-2019 were enrolled. The patients were divided into two groups according to whether OSA was combined. STOP-Bang questionnaire scoring system was used to classify patients into high risk and low risk for OSA. The differences between perioperative management and complications between the two groups were compared. Results: 308 consecutive cases were included, 46 cases (14.9%) combined with OSA and 108 cases (35.0%) were at high risk of OSA. OSA patients have higher morbidity of hypertension (OR, 2.05; CI, 1.07-3.92; P=0.03), hyperlipidemia (OR, 2.19; CI, 1.06- 4.51; P=0.03), longer hospitalization time(7.0±2.7 vs. 5.4±3.6, P≤0.01) and higher incidence of intubation difficulties (OR, 3.74; CI, 1.39-10.1; P=0.01). Patients at high risk of OSA also had increased rates of hypertension, hyperlipidemia, coronary heart disease and post-operative cardiovascular and respiratory complications. Conclusion: OSA or high scores of STOP-Bang are associated with increased perioperative complications in ESS patients. Preoperative OSA screening should be strengthened to improve the safety and prognosis of ESS surgery. Support: National Natural Science Foundation of China under Grant [number 81670903]; and Beijing Municipal Administration of Hospitals Ascent Plan under Grant [number DFL20150602]